Case Report: A Calculus-Free Ureteral Stent Forgotten for 29 Years - Cheng Tang; Genyi Qu; Guang Yang; Gang Wang; Yong Xu (Frontiers in Surgery, 2022)
Ureteral stents are widely used. If ureteral stents remain in place for extended periods, the probability of migration and stone formation increases substantially. However, a 29-year-old ureteral stent that was placed and did not develop calculus is rare. We reported a 45-year-old man admitted with pain in the left side of his waist and abdomen for more than 10 years. He underwent a ureterotomy 29 years prior to admission for left ureteral calculi, and a ureteral stent was placed postoperatively to prevent ureteral strictures. The ureteral stent was not removed in the hospital due to poor compliance on the part of the patient. This left ureteral stent was not visible on computed tomography (CT) and plain films. On ureteroscopy or flexible ureteroscopy, no new calculus was found in the left ureter and kidney. No calculus was found in the stent that is usually easily removed with calculus-removing forceps. This phenomenon is rare, and it highlights the importance of follow-up.